Pelatihan Desain Canva dan Google Drive Dalam Pengelolaan Strategi Promosi - Mutmainah; Andik Susanto (JURNAL DAYA-MAS, 2024)
One thing that attracts people to make purchases is product photos. Producing excellent and attractive product photos requires extra effort in designing and editing them. An application is needed that can help entrepreneurs, especially "UMKM," to be able to create product photos more quickly, practically, and with excellent and attractive results. The community service team introduces and trains the use of the Canva application to answer the needs of these business actors. The team also introduced and trained on maximizing the use of the Google Drive application on cellphones to help "UMKM," store document or photo files. The activity was carried out at the UMKM Corner Gallery in Madiun City using lecture, discussion, and practice methods. Participants who are "UMKM" in the Madiun Regency area support this activity, as seen from those willing to attend during busy activities. The activity ran well and smoothly; the participants' enthusiasm for participating could be seen from the design of the product photos, which were produced in more than one photo and shared on their social media. Active discussions and questions and answers are also a form of their enthusiasm. This training activity lets the service team know what “UMKM”business actors need.